EFFECTIVENESS OF VICTIM PROTECTION IN HUMAN TRAFFICKING CRIMES: A REVIEW OF INTERNATIONAL CRIMINAL LAW - Wang, Wesly; Firmansyah, Hery (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Human trafficking as a transnational crime requires legal responses aligned with international standards, particularly the Palermo Protocol. Victim protection is a critical aspect considering the vulnerability of victims' positions. This study aims to analyze the effectiveness of victim protection in human trafficking cases in Indonesia and assess its compliance with international criminal law principles. The research method employs a normative legal approach through legislative studies, conceptual analysis, and literature review of national and international legal frameworks. Data were collected through document studies, doctrinal analysis, and interviews with legal practitioners to deepen understanding of implementation issues. The research findings indicate that although victim protection has been normatively regulated under Law No. 21 of 2007 and the authority of the Witness and Victim Protection Agency (LPSK), its implementation remains ineffective. Challenges include limitations in ongoing assistance, minimal asset tracing mechanisms, weak fulfillment of restitution rights, and suboptimal inter-agency coordination. Compared to international standards, protection in Indonesia remains procedural and does not yet reflect a holistic approach in accordance with the 3P principles (prevention, protection, prosecution). The study concludes that there is a gap between legal norms and the implementation of victim protection.